Control of partial differential equations and applications proceedings of the IFIP TC7/WG-7.2 international conference, Laredo, Spain - Casas, Eduardo (Lecture notes in pure and applied mathematics, 1996)
Based on the International Federation for Information Processing TC7/WG-7.2 Conference, held recently in Laredo, Spain, this invaluable reference provides the latest theoretical advances as well as the most recent results on numerical methods and applications of control for partial differential equations. Containing key literature citations and some 1350 equations, Control of Partial Differential Equations and Applications is an incomparable resource for pure and applied mathematicians, mathematical analysts, geometers, control and electrical and electronics engineers and scientists, physicists, computer scientists, and graduate-level students in these disciplines.